Case law of the European court of human rights on compensation for non-pecuniary damage: Certain issues - Vitalii, Makhinchuk; Volodymyr, Bobryk; Denys, Pozov; Oleksandra, Karmaza; Sergii, Koroied (Edelweiss Applied Science and Technology, 2024)
Compensation is considered a means of restoring the violated rights. Ukrainian legislation directly provides for the possibility of compensation for non-pecuniary damage, however, a number of problems arise when considering cases on this issue in national courts. Firstly, there is no legally enshrined definition of this concept in Ukraine. Secondly, there is no single methodology or model for assessing moral damage, no formula for calculation is established at the legislative level, due to which judges assign different amounts of compensation for harm caused under the same or similar circumstances. Besides, there are no clear criteria for determining the amount of damage caused, which makes it almost impossible to unambiguously calculate, for example, the extent of the mental pain or the infringement on dignity and honor in property equivalent, that is, it is in fact a conditional compensation. Reference to the case law of the ECHR on this matter may contribute to solving these problems, because its decisions are referred to by national courts. The ECHR has not developed a universal formula for calculating the amount of non-pecuniary damage, but there are certain criteria for its assessment: the nature of the offense and violated right; payments accrued based on the results of consideration of previous cases; victim’s personality; the respondent State; collective statements or mass offenses; other circumstances of the case.